Heparan sulfate and cell division - Porcionatto,M.A. (1999)
Heparan sulfate is a component of vertebrate and invertebrate tissues which appears during the cytodifferentiation stage of embryonic development. Its structure varies according to the tissue and species of origin and is modified during neoplastic transformation. Several lines of experimental evidence suggest that heparan sulfate plays a role in cellular recognition, cellular adhesion and growth control. Heparan sulfate can participate in the process of cell division in two distinct ways, either as a positive or negative modulator of cellular proliferation, or as a response to a mitogenic stimulus.